1972
DOI: 10.1017/s004317450003527x
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of Siduron Tolerance in Foxtail Barley

Abstract: Thirty-six collections of foxtail barley(Hordeum jubatumL.) from North Dakota, South Dakota, Minnesota, Wisconsin, and Montana varied in susceptibility to 1-(2-methylcyclohexyl)-3-phenylurea (siduron) as determined from radicle elongation of treated seeds. Data from F2seedlings of crosses between tolerant and susceptible selections indicated that three complementary dominant factors control the inheritance of siduron tolerance in foxtail barley. Evolution of siduron-tolerant foxtail barley could occur from sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

1973
1973
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Varietal differ-ences in response to herbicides have been shown previously in other genera (Hopen & Splittstoesser, 1968;Hardcastle, 1974). For example, Schooler, Bell & Nalewaja (1972) reported that tolerance to siduron[l-(2-methylcyclohexy])-3-phenylurea] varied among thirty-six ecotypes of foxtail barley {Hordeum jubatum L.). Since the degree of tolerance was genetically controlled, siduron-tolerant foxtail barley probably developed from selection pressure arising from the extensive use of the herbicide siduron.…”
Section: Introductionmentioning
confidence: 66%
“…Varietal differ-ences in response to herbicides have been shown previously in other genera (Hopen & Splittstoesser, 1968;Hardcastle, 1974). For example, Schooler, Bell & Nalewaja (1972) reported that tolerance to siduron[l-(2-methylcyclohexy])-3-phenylurea] varied among thirty-six ecotypes of foxtail barley {Hordeum jubatum L.). Since the degree of tolerance was genetically controlled, siduron-tolerant foxtail barley probably developed from selection pressure arising from the extensive use of the herbicide siduron.…”
Section: Introductionmentioning
confidence: 66%
“…Plants from both locations were susceptible to other nontriazine herbicides. Data presented by Schooler, Bell, and Nalewaja (1972 These reports suggest that increased herbicide tolerance within a weed species may result from repeated applications by elimination of sensitive types and indicate a need for herbicide rotations when possible.…”
mentioning
confidence: 99%
“…Also, multiple genes, each partially contributing to the overall phenotype, have been documented conferring tolerance. For example, siduron tolerance in foxtail barley (Hordeum jubatum L.) was found to be controlled by at least three dominant complementary major genes (Schooler et al 1972). Quantitative patterns of variation in response to herbicides were also observed in common flax (Linum usitatissimum L.), when exposed to atrazine and MCPA (Comstock and Andersen 1968;Stafford et al 1968), although this variation was concluded to be mainly due to environmental factors.…”
Section: Introductionmentioning
confidence: 99%